Disentangling the facets of sharing: A categorization of what we know and don't know about the Sharing Economy. Issue 4 (6th August 2018) - Trenz, Manuel; Frey, Alexander; Veit, Daniel
Abstract : Purpose: The purpose of this paper is to develop a categorization of sharing practices from a structured interdisciplinary literature review on the Sharing Economy. Instead of striving for a new definition, the authors distinguish nine types of sharing practices and provide an overview of prior investigations on sharing practices across three levels of analysis and 15 research areas. The structured analysis is translated into opportunities for future research on the Sharing Economy. Design/methodology/approach: The study follows a structured literature review approach to uncover practices related to the Sharing Economy and similar phenomena. The authors analyze 210 articles from a broad number of disciplines, and develop a categorizing framework for Sharing Economy practices. Findings: The paper identifies nine different types of sharing practices and provides a structured way for analyzing, comparing and positioning research on the Sharing Economy and related phenomena. Research limitations/implications: The categorization of sharing practices and the embedded interdisciplinary overview of studies on the Sharing Economy help to explain potentially contradictory research results and uncovers opportunities for future research in the topic area. Originality/value: Given the variety of disciplines dealing with the Sharing Economy and the plenitude of definitions and related concepts, the categorization and research overview provides a consolidated view of the knowledge in the topic area and an effective tool for identifying paths for future research.